Improved nutrition in adolescents and young adults after childhood cancer - INAYA study. Issue 1 (December 2016) - Quidde, J.; von Grundherr, J.; Koch, B.; Bokemeyer, C.; Escherich, G.; Valentini, L.; Buchholz, D.; Schilling, G.; Stein, A.
Abstract Background Multimodality treatment improves the chance of survival but increases the risk for long-term side effects in young cancer survivors, so-called" Adolescents and Young Adults"(AYAs). Compared to the general population AYAs have a 5 to 15-fold increased risk of cardiovascular morbidity. Thus, improving modifiable lifestyle risk factors is of particular importance. Methods The INAYA trial included AYAs between 18 and 39 years receiving an intensified individual nutrition counseling at four time points in a 3-month period based on a 3-day dietary record. At week 0 and 12 AYAs got a face-to-face counseling, at week 2 and 6 by telephone. Primary endpoint was change in nutritional behavior measured by Healthy Eating Index - European Prospective Investigation into Cancer and Nutrition (HEI-EPIC). Results Twenty-three AYAs (11 female, 12 male, median age 20 years (range 19–23 years), median BMI: 21.4 kg/m2 (range: 19.7–23.9 kg/m2 ) after completion of cancer treatment for sarcoma (n  = 2), carcinoma (n  = 2), blastoma (n  = 1), hodgkin lymphoma (n  = 12), or leukemia (n  = 6) were included (median time between diagnosis and study inclusion was 44 month). The primary endpoint was met, with an improvement of 20 points in HEI-EPIC score in 52.2 % (n  = 12) of AYAs. At baseline, median HEI-EPIC score was 47.0 points (range from 40.0 to 55.0 points) and a good, moderate and bad nutritional intake was seen in 4.3, 73.9 and 21.7 % of AYAs. At week 12, median HEI-EPIC improved significantly to 65.0 points (range from 55.0 to 76.0 points) (p  ≤ 0.001) and a good, moderate and bad nutritional intake was seen in 47.8, 52.2 and 0 % of AYAs. No change was seen in quality of life, waist-hip ratio and blood pressure. Conclusion Intensified nutrition counseling is feasible and seem to improve nutritional behavior of AYAs. Further studies will be required to demonstrate long-term sustainability and confirm the results in a randomized design in larger cohorts. Trial registration Clinical trial identifierDRKS00009883 on DRKS